Use of "free station" method in geodetic support of high-rise building construction - Borgekova, Қарлығаш (Рroblems of engineering and professional education, 2023)
This article discusses the "free station" method, which is effective in creating reference geodetic points on building horizons, moving elements of a building structure to the design position, executive survey, geodetic observations.